1985
DOI: 10.1200/jco.1985.3.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Lorazepam in cancer patients treated with cisplatin: a drug having antiemetic, amnesic, and anxiolytic effects.

Abstract: There currently is no pharmacologic approach to the problem of anticipatory nausea and vomiting (ANV). Lorazepam (Ativan, Wyeth Laboratories, Philadelphia) is an interesting candidate drug if it could block the recall of the unpleasant events associated with chemotherapy, especially if it also has antiemetic properties. Since ANV is a conditioned (learned) response, it may well depend on a memory imprint of the stimulus. This pilot study was designed to use intravenous lorazepam given before and after cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…18 The use of medications including vitamin B6, ondansetron, promethazine, metoclopramide, dexamethasone, famotidine, and droperidol, alone or in combination, has been reported in the literature of CHS patients but has failed to effectively relieve the symptoms of nausea and vomiting. 7,9,18 Lorazepam's antiemetic, amnestic, and anxiolytic properties have made it useful for the treatment of anticipatory nausea and vomiting in patients undergoing chemotherapy 20 and in patients with cyclic vomiting syndrome. 21 The effectiveness of lorazepam in the relief of nausea and vomiting symptoms in CHS patients has been reported in 2 recent case reports.…”
Section: Management Of Chs Patientsmentioning
confidence: 99%
“…18 The use of medications including vitamin B6, ondansetron, promethazine, metoclopramide, dexamethasone, famotidine, and droperidol, alone or in combination, has been reported in the literature of CHS patients but has failed to effectively relieve the symptoms of nausea and vomiting. 7,9,18 Lorazepam's antiemetic, amnestic, and anxiolytic properties have made it useful for the treatment of anticipatory nausea and vomiting in patients undergoing chemotherapy 20 and in patients with cyclic vomiting syndrome. 21 The effectiveness of lorazepam in the relief of nausea and vomiting symptoms in CHS patients has been reported in 2 recent case reports.…”
Section: Management Of Chs Patientsmentioning
confidence: 99%
“…Some studies have reported up to 30% of anticipa tory emesis in repeated cycles of chemotherapy with a close link between anticipatory emesis and anxiety being established [22], The addition of a benzodiaze pine in combination with metoclopramide and dexamethasone leads to a reduction of the patient's an xiety, with lower anticipatory emesis rate [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Diphenhydramine was for merly added to the high-dose metoclopramide-dexamethasone combination to abrogate the extrapyramidal effects inherent in the antidopaminergic proper ties of metoclopramide. In later studies, the trend was to use lorazepam instead of diphenhydramine, due to the antianxiety benefit observed in some trials, dimin ishing anticipatory emesis [5][6][7] and its effect on the cerebral cortex [8].…”
Section: Introductionmentioning
confidence: 99%
“…10) Benzodiazepines, most commonly lorazepam and diazepam, have been administered as antiemetics to prevent ANV. 11,12) There has been a case report on the use of clonazepam (a benzodiazepine) as an antiemetic. Koga et al 13) reported that a patient suffered from refractory CINV despite extensive antiemetic therapy, but fully recovered after taking clonazepam.…”
mentioning
confidence: 99%